2016
DOI: 10.1182/blood-2016-04-709519
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib inhibits CD20 upregulation on CLL B cells mediated by the CXCR4/SDF-1 axis

Abstract: Key Points• Microenvironmental interactions upregulate CD20 expression in CLL cells through the CXCR4/SDF-1 axis.• Ibrutinib treatment causes downregulation of CD20 in CLL cells.Agents targeting B-cell receptor (BCR) signaling-associated kinases such as Bruton tyrosine kinase (BTK) or phosphatidylinositol 3-kinase can induce mobilization of neoplastic B cells from the lymphoid tissues into the blood, which makes them potentially ideal to combine with anti-CD20 monoclonal antibodies (such as rituximab, obinutuz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
94
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 24 publications
7
94
0
Order By: Relevance
“…CXCR4 is an alphachemokine receptor specific for stromal-derived-factor-1 (SDF-1 also called CXCL12), a molecule endowed with potent chemotactic activity for lymphocytes. It has been reported that CXCR4 signaling regulated the expression of CD20 on B cells [32]. Evidence in animal model suggested the ubiquitin was the natural ligand of CXCR4 and it was anti-inflammatory immune modulator and endogenous opponent of pro-inflammatory damage associated molecular pattern molecules [33], suggesting that CXCR4 was involved in the immune response.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…CXCR4 is an alphachemokine receptor specific for stromal-derived-factor-1 (SDF-1 also called CXCL12), a molecule endowed with potent chemotactic activity for lymphocytes. It has been reported that CXCR4 signaling regulated the expression of CD20 on B cells [32]. Evidence in animal model suggested the ubiquitin was the natural ligand of CXCR4 and it was anti-inflammatory immune modulator and endogenous opponent of pro-inflammatory damage associated molecular pattern molecules [33], suggesting that CXCR4 was involved in the immune response.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Previous reports demonstrated that ibrutinib could disrupt the interaction between CLL cells and tumor microenvironment by decreasing chemokines such as C‐X‐C motif chemokine ligand 12 (CXCL12) and C‐X‐C motif chemokine ligand 13 (CXCL13) secreted by macrophages and downregulating the expression of C‐X‐C chemokine receptor type 4 (CXCR4) but not C‐X‐C chemokine receptor type 5 (CXCR5) and CD49d on the surface of CLL cells . Simultaneous downregulation of CD20 expression on CLL cells was also observed as a result of CXCR4 inhibition . Moreover, ibrutinib has been found to help restore host immunity by increasing T cell number and repertoire diversity, improving T cell function, suppressing immunosuppressive molecule ligands such as programmed death‐ligand 1 (PD‐L1) on cancer cells, and eliminating BTK‐expressed myeloid‐derived suppressor cells (MDSC) .…”
Section: Introductionmentioning
confidence: 99%
“…And it is expressed in T cells, macrophages, dendritic cells chronically [37]. Analogously, CXCR4 refers to the ligands such as SDF-1 and ubiquitin, etc [38,39]. And it is also widely expressed in cells as CD4+ T cells, dendritic cells, microglia and glomerular podocytes, etc [40].…”
Section: A Comprehensive Vista: Molecular Cocktailmentioning
confidence: 99%